2009
DOI: 10.1152/ajprenal.90722.2008
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected effect of angiotensin AT1receptor blockade on tubuloglomerular feedback in early subtotal nephrectomy

Abstract: Singh P, Deng A, Blantz RC, Thomson SC. Unexpected effect of angiotensin AT1 receptor blockade on tubuloglomerular feedback in early subtotal nephrectomy. Am J Physiol Renal Physiol 296: F1158 -F1165, 2009. First published February 11, 2009 doi:10.1152/ajprenal.90722.2008.-After subtotal nephrectomy (STN), the remaining nephrons engage in hyperfiltration, which may be facilitated by a reduced sensitivity of the tubuloglomerular feedback (TGF) response to increased distal delivery. However, a muted TGF respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…7 We confirmed this finding in the current study and also showed normal tubuloglomerular feedback responses in UN. Furthermore, we have shown that preserving normal tubuloglomerular feedback in STN with losartan diminished the functional resistance of STN.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…7 We confirmed this finding in the current study and also showed normal tubuloglomerular feedback responses in UN. Furthermore, we have shown that preserving normal tubuloglomerular feedback in STN with losartan diminished the functional resistance of STN.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic angiotension I receptor blockade was achieved by adding losartan (200 mg/L) to the drinking water. 7 Placebo controls were given a water bottle with no losartan. For HIF induction, CoCl 2 was administered at 30 mg/kg two times a day subcutaneously for 2 days, with the last dose 6 hours before IR.…”
Section: Concise Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, for hyperfiltration to endure, some alteration of the TGF system becomes necessary. When we examined TGF activity at early stages after STN in rats, no TGF response was observed (42). Furthermore, paradoxical restoration of TGF response in STN was observed with angiotensin II blockade, as typically, TGF response is subdued by blocking angiotensin II.…”
Section: Pathophysiology Of Ckdmentioning
confidence: 96%